Dlaczego współczesny uniwersytet potrzebuje controllingu? - Krawiec, Magdalena (Why Modern Universities Need Controlling?, 2006)
The article brings up the theme of adapting business solutions to management systems in higher education, in this case universities. It briefly describes controlling instruments which can be used in management of universities. Moreover, the paper draws reader's attention to the most important factors determining a manner and a form of implementing this system.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1101, s. 203-210